2016
DOI: 10.1007/s10068-016-0125-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sucrose fatty acid esters with different hydrophilic-lipophilic balance values on pasting and rheological properties of waxy rice flour

Abstract: Effects of sucrose fatty acid esters (SEs) with hydrophilic-lipophilic balance (HLB) values of 5 (S-570), 9 (S-970), and 15 (S-1570) on the pasting and rheological properties of waxy rice flour (WRF) were investigated. Rapid Visco Analyzer (RVA) showed that addition of SEs affected the pasting properties of WRF. Rheological experiment includes the steady shear flow characteristics, and dynamic viscoelastic properties were also determined using a controlled-stress rheometer. The steady shear tests demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The larger the amount of sucrose that is added, the lower the ability of the quinoa paste to hinder the flow, and the lower the viscosity of the quinoa paste. The quinoa paste is easy to disperse and dissolve during brewing under these conditions (Fang, Zuo, Xu, Meng, & Liu, ). In the present study, the viscosity of puffed full flour, puffed peeled flour, and puffed traditional flour decreased with an increase in sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…The larger the amount of sucrose that is added, the lower the ability of the quinoa paste to hinder the flow, and the lower the viscosity of the quinoa paste. The quinoa paste is easy to disperse and dissolve during brewing under these conditions (Fang, Zuo, Xu, Meng, & Liu, ). In the present study, the viscosity of puffed full flour, puffed peeled flour, and puffed traditional flour decreased with an increase in sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…The pasting properties of starch are mainly related to the swelling and rupture of the starch granules during heating in the excess water (Fang et al., 2016). The pasting parameters of cornstarch by adding sucrose esters with different HLB values (CSSE) are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As the HLB value increased, the proportion of monostearate in sucrose was increased, while the proportion of di‐stearate and tri‐stearate was decreased. This suggested that SE with a high HLB value showed a better linear structure and a less steric hindrance than that with a low HLB value, which could form more robust gel network through hydrogen bonds that contributed to the increase in the PV, TV, and FV values (Fang et al., 2016; Meng et al., 2014). Another reason may be due to the fact that the SE can easily form a stable complex with the leached amylose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it can also play a role in influencing the behavior of liquid PS flow. The possibility of Amylose-lipid complex formation also plays an important role in decreasing viscosity because this formation could inhibit amylose network development [33].…”
Section: Flow Behavior Of Grf-cm-ps Pastementioning
confidence: 99%